The Heutagogy Model of Learning Innovation in Increasing The Skill Needs of The Digital Era of Vocational Students - Yoto, Yoto; Ulfatin, Nurul Rahma; Zahro, Azizatuz; Putra, Andika Bagus; Subandi, Mahfudi Sahly; Rochmawati, Rochmawati; Santoso, Aman (Jurnal Ilmu Pendidikan, 2022)
The digital technology-based heutagogy learning model characterizes the progress of implementing vocational education in a nation. This study aims to develop a heutagogy learning model for vocational students through mapping its components. The method in this study uses descriptive qualitative. Research subjects include university lecturers, vocational high school teachers, and industrial employees. The research location is focused on East Java. The research instrument consisted of a questionnaire and documentation. The heutagogy component for vocational students includes critical thinking, collaboration skills, communication skills, and creativity. Mapping the four components supporting the application of the heutagogy learning model needs to be done to improve the quality of vocational students in the digital era